Model for the Analysis of the Company Performance - Mădălina DUMBRAVĂ (Theoretical and Applied Economics, 2010)

(untitled)
The analysis of the performance of a firm (company) has a determinant role in setting the strategy to follow and this is more necessary during the period of economic-financial crisis. In the following items, I have performed the analysis, based on the balance sheet data, for SC DELTA SRL, using a system of indicators that have relevance, and the interpretation of which allows to draw certain conclusions, depending on which the future development can be forecasted. I have tried to use a number of indicators, viewed as a system, which would define, in the end, a model for company performance analysis. The research focused on using the system of indicators on the data from the balance sheet of SC DELTA SRL.